Oxygen alert cards and controlled oxygen: preventing emergency admissions at risk of hypercapnic acidosis receiving high inspired oxygen concentrations in ambulances and A&E departments. Issue 8 (20th July 2006) - Gooptu, B; Ward, L; Ansari, S O; Eraut, C D; Law, D; Davison, A G
Abstract : Background: Appropriate resuscitation of hypoxic patients is fundamental in emergency admissions. To achieve this, it is standard practice of ambulance staff to administer high concentrations of oxygen to patients who may be in respiratory distress. A proportion of patients with chronic respiratory disease will become hypercapnic on this. Objectives and methods: A scheme was agreed between the authors' hospital and the local ambulance service, whereby patients with a history of previous hypercapnic acidosis with a P ao 2 >10.0 kPa—indicating that oxygen may have worsened the hypercapnia—are issued with "O2 Alert" cards and a 24% Venturi mask. The patients are instructed to show these to ambulance and A&E staff who will then use the mask to avoid excessive oxygenation. The scheme was launched in 2001 and this paper present the results of an audit of the scheme in 2004. Results: A total of 18 patients were issued with cards, and 14 were readmitted on 69 occasions. Sufficient documentation for auditing purposes was available for 52 of the 69 episodes. Of these audited admissions, 63% were managed in the ambulance, in line with card-holder protocol. This figure rose to 94% in the accident and emergency department. Conclusion: These data support the usability of such a scheme to prevent iatrogenic hypercapnia in emergency admissions.